P-021 National trends in the U.S. of endovascular intra-arterial thrombectomy and related mortality following acute ischemic stroke in patients less than 80 years old compared to their older counterparts. (22nd July 2018) - Aly, A; Ali, M; Zitterkopf, Z; Aurit, S; Stavas, J; Mironov, A
Abstract : Introduction: The beneficial effect of endovascular thrombectomy in acute ischemic stroke has been proven effective in multiple trials. Recommendations regarding patient criteria and treatment window are frequently updated allowing inclusion of more patients in the treatment group. Elderly patients older than 80 years old have been largely excluded in multiple trials while the ongoing aging of the population will increase this subgroup for stroke management in many medical practices. Prior retrospective studies showed the mortality related thrombectomy was higher in octogenarians, but these conclusions where based on old data (pre-2011) and prior to technological advances and greater practitioner experience. We evaluated the national trends of performing thrombectomy and subsequent inpatient mortality in people less than 80 years old with ischemic stroke compared to their older counterparts. Methods: The National Inpatient Sample (NIS) database identified hospitalizations from 2006 to 2014 with ICD-9 codes for acute ischemic stroke and endovascular thrombectomy. Annual trends of thrombectomy for stroke patients≥80 years old were compared to those <80 years; inpatient mortality after thrombectomy was analyzed in a similar manner. Multivariable binary logistic regression was used to adjust for patient and facility-level characteristics to model mortality for those whom underwent thrombectomy. SAS v9.4 (Cary, NC) and Joinpoint Trend Analysis v4.5 software packages were used for all analyses. All analyses accounted for the NIS sampling design. Results: There were 3, 821, 234 total hospitalizations associated with acute ischemic stroke between 2006–2014 and the total thrombectomy rate was 0.71%, including patients≥80 years old (n=6, 042) and patients<80 years (n=21, 382). Thrombectomy treatments increased in both age groups. For the older patient cohort, a 24.14 annual percent change (APC) increase was observed from 2008 to 2014 (2.8 to 10.1 procedures per 1000 stroke admissions); for younger patients a 16.8 APC increase was observed during the same time frame (5.7 to 14.5 procedures per 1000 stroke admissions). Risk of inpatient mortality was higher in the elderly group (OR 1.6, 1.34–1.94) after adjusting for patient and facility-level characteristics. Yet, older patients with thrombectomy showed 6.6 APC decrease in mortality from 2008 to 2014. Conclusion: Overall mortality continued to be higher in people≥80 years old when compared to their younger counterparts following acute ischemic strokes. However, there was a notable trend of decreasing thrombectomy related mortality across all age groups over the years, suggesting minimally invasive neuro-interventional techniques are feasible in older stroke populations. Disclosures: A. Aly: None. M. Ali: None. Z. Zitterkopf: None. S. Aurit: None. J. Stavas: 2; C; inRegen Biotechnology, Excelerate Health Ventures. A. Mironov: None.